2018
DOI: 10.1002/lary.27262
|View full text |Cite
|
Sign up to set email alerts
|

Negative Pressure Wound Therapy in the Head and Neck: An Evidence‐Based Approach

Abstract: Negative pressure wound therapy is useful for the management of head and neck wounds and should be considered for patients in whom wound healing is progressing insufficiently, including those with a history of head and neck cancer, oro-/pharyngocutaenous fistula, and trauma. Randomized controlled trials further comparing NPWT versus other modalities may be invaluable in further delineating its appropriate role. Laryngoscope, 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 67 publications
0
28
0
Order By: Relevance
“…In the era of evidence based medicine, Mir et al, [11] yielded in a review 522 cases of NPWT use in head and neck in 57 studies. The total number of trauma cases in all studies (13) was astonishingly only 50 cases in all studies.…”
Section: Discussionmentioning
confidence: 99%
“…In the era of evidence based medicine, Mir et al, [11] yielded in a review 522 cases of NPWT use in head and neck in 57 studies. The total number of trauma cases in all studies (13) was astonishingly only 50 cases in all studies.…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy of NPWT/VAC therapy for all kinds of head and neck wounds has been recently reviewed in an excellent paper [ 32 ]. One problem is the definition of the outcome.…”
Section: Discussionmentioning
confidence: 99%
“…The intended use was to facilitate granulation tissue formation until subsequent reconstruction using skin graft or local flaps. Mir et al labelled the response to be 100% when there was either complete closure or granulation tissue formation and otherwise a failed or 0 response [36]. The studies in cumulative series showed a mean response rate of 88.2% (82.2 ± 10.4).…”
Section: Discussionmentioning
confidence: 99%